2022
DOI: 10.1182/bloodadvances.2021006415
|View full text |Cite
|
Sign up to set email alerts
|

Risk profiling of patients with relapsed/refractory diffuse large B-cell lymphoma by measuring circulating tumor DNA

Abstract: Patients with relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL) have heterogeneous outcomes; durable remissions are infrequently observed with standard approaches. Circulating tumor DNA (ctDNA) assessment is a sensitive, potentially prognostic tool in this setting. We assessed baseline ctDNA to identify patients with R/R DLBCL at high risk of relapse after receiving polatuzumab vedotin and bendamustine + rituximab (BR), or BR alone. Patients were transplant-ineligible and had received ≥1 prior li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…However, we observed that patients with a lower BMI had a higher frequency of CR than those with a higher BMI (66.7 & 81.4% vs 51.3%, p = 0.002). This finding is in contrast to some studies that reported a positive correlation between BMI and CR in patients with DLBCL [ 23 ], but in agreement with others that found no association or a negative correlation [ 24 ]. The possible mechanisms underlying the relationship between BMI and CR are not clear, but may involve the pharmacokinetics of R-CHOP drugs, the inflammatory status of obese patients, or the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 81%
“…However, we observed that patients with a lower BMI had a higher frequency of CR than those with a higher BMI (66.7 & 81.4% vs 51.3%, p = 0.002). This finding is in contrast to some studies that reported a positive correlation between BMI and CR in patients with DLBCL [ 23 ], but in agreement with others that found no association or a negative correlation [ 24 ]. The possible mechanisms underlying the relationship between BMI and CR are not clear, but may involve the pharmacokinetics of R-CHOP drugs, the inflammatory status of obese patients, or the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 81%
“…However, the lack of correlation between CD79b expression (as measured by IHC) and the clinical response to Polivy ® [ 87 ] suggests that further research is required to elucidate suitable biomarkers to predict the response to Polivy ® . One potential prognostic tool is the level of circulating tumour DNA (ctDNA) in the periphery, with high baseline ctDNA being an indicator of a high risk of lymphoma progression [ 92 ].…”
Section: Features Of Antigens For Antibody Target Selection In Adc De...mentioning
confidence: 99%
“…A key challenge of ctDNA based liquid biopsy approaches is identifying the optimal way to represent tumor load. Some reports have quanti ed ctDNA serially as allele frequency (AF), and some others have evaluated mutant molecules per mL plasma (MMPM) 8,9 . In our study, we assessed ctDNA dynamics during multiple time points across standard of care therapy in 25 patients with advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%